2014
DOI: 10.1242/jcs.142539
|View full text |Cite
|
Sign up to set email alerts
|

α-Arrestins – new players in Notch and GPCR signaling pathways in mammals

Abstract: For many years, b-arrestins have been known to be involved in G-protein-coupled receptor (GPCR) desensitization. However, barrestins belong to a family of proteins that act as multifunctional scaffolding proteins, in particular during trafficking of transmembrane receptors. The arrestin family comprises visual arrestins, b-arrestins and a-arrestins. In mammals, the functions of the a-arrestins are beginning to be elucidated, and they are described as versatile adaptors that link GPCRs or the Notch receptor to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
75
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(79 citation statements)
references
References 82 publications
4
75
0
Order By: Relevance
“…ARRDC3 possesses arrestin-like N-and C-domains and Cterminal PPxY motifs that bind to WW domains of HECT-domain containing E3 ubiquitin ligases (48,49). Despite the presence of arrestin-like domains, the α-arrestin ARRDC3 appears to lack a polar core, which is essential for β-arrestin binding to activated and phosphorylated GPCRs (50). In addition, β-arrestins lack C-terminal PPxY motifs, indicating that a-arrestin and b-arrestin proteins likely have divergent functions.…”
Section: Discussionmentioning
confidence: 99%
“…ARRDC3 possesses arrestin-like N-and C-domains and Cterminal PPxY motifs that bind to WW domains of HECT-domain containing E3 ubiquitin ligases (48,49). Despite the presence of arrestin-like domains, the α-arrestin ARRDC3 appears to lack a polar core, which is essential for β-arrestin binding to activated and phosphorylated GPCRs (50). In addition, β-arrestins lack C-terminal PPxY motifs, indicating that a-arrestin and b-arrestin proteins likely have divergent functions.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies classified the arrestin family into visual-arrestins, β-arrestins (e.g., β-arrestin2), and α-arrestins (ARRDCs in mammals) [44]. Although α-arrestins are mainly membrane-associated proteins, recent studies indicated that they change their subcellular localization in response to different stimuli [44].…”
Section: Discussionmentioning
confidence: 99%
“…Second, SIMPLE interacts with Nedd4 E3 ubiquitin ligases via the PPXY motifs (34,37). PPXY motifs are also found in all of the ␣-arrestin proteins except the Arrdc5 member (79,80). Third, SIMPLE encodes a PTAP motif for its interaction with ESCRT-1 protein Tsg101 (34,37).…”
Section: Discussionmentioning
confidence: 99%